Influence of Biological Factors and Types of Food on the Growth and Development of Teeth of Preschool Children – A walk in analysis - R Sabda Alam (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
The growth and development of teeth in preschool children is influenced by various factors, including biological aspects and the type of food consumed, both of which are crucial for overall child development. This study aimed to analyze these influences on 69 preschool children examined at Jemursari Islamic Hospital Surabaya between January and December 2024, using a descriptive approach with an observational method. Data collection involved questionnaires filled out by parents regarding diet, health history, and biological factors, while dental examinations were conducted by dentists to assess dental health. The findings indicated a significant relationship between food consumption and children's dental health, where those who frequently consumed sugary foods had a higher risk of dental caries. Additionally, biological factors such as the mother's health history during pregnancy also played a role in determining a child’s dental condition. Given these findings, it is essential for parents to recognize the importance of biological factors and diet in supporting optimal dental growth and development. A balanced diet and proper dental care are necessary to prevent future dental issues. However, this study was limited to a single location with a sample of 69 children and did not consider broader environmental factors. The results highlight the need to enhance parental awareness regarding children's nutrition and dental health, emphasizing the importance of educational programs on healthy eating habits and oral hygiene, especially for parents of preschool children.